ANALISIS PENGARUH SOCIAL MEDIA MARKETING DAN INFLUENCER MARKETING TERHADAP BRAND LOYALTY DENGAN BRAND TRUST DAN BRAND EQUITY SEBAGAI MEDIASI - Maria Verena Emeralda; Kurniawati Kurniawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is aimed to analyze the impact of social media marketing and influencer marketing to brand loyalty with brand trust and brand loyalty as mediating variables within local skincare industry in Indonesia. Total of 349 questionnaire responses were collected by non-probabilistic sampling in skincare communities across the country within 2 months period. Hypothesis was analyzed with SEM-PLS method and Barron & Kenny method using AMOS. Research finding shows that social media marketing and influencer marketing has positive impacts to brand trust and brand equity. However, brand loyalty was only affected positively by influencer marketing. Secondly, brand trust and brand equity partially mediated social media marketing with brand loyalty but brand trust and brand equity failed to mediate the connection between influencer marketing with brand loyalty.